2016
DOI: 10.7314/apjcp.2016.17.3.1235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a School-based Intervention Program on Attitude and Knowledge of Household Members Towards a Smoke-free Home: a Cluster Controlled Trial

Abstract: Background: A school-based smoke free home (SFH) program is useful in empowering the mother and child to reduce secondhand smoke exposure but the effects of pretesting on knowledge and attitude has been largely ignored. We aimed to test whether such a program can be effective in Southern Thailand with an additional assessment of the net effect of the pretest. Materials and Methods: A Solomon four-group design was used. Twelve rural primary schools were assigned to one of the four conditions (each with 3 school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…However, most of these studies occurred in schools or primary care settings rather than in the workplace [34][35][36]. Similarly, some school-based intervention studies also found significant effects on changing both smoking-related knowledge and attitudes [34,35]. Other school-based intervention studies reported [36] that despite smoking knowledge increasing substantially over the follow-up, the attitudes did not change, mainly because attitudes were more stable than knowledge and more resistant to change.…”
Section: Smoking-related Knowledge and Attitudesmentioning
confidence: 98%
See 1 more Smart Citation
“…However, most of these studies occurred in schools or primary care settings rather than in the workplace [34][35][36]. Similarly, some school-based intervention studies also found significant effects on changing both smoking-related knowledge and attitudes [34,35]. Other school-based intervention studies reported [36] that despite smoking knowledge increasing substantially over the follow-up, the attitudes did not change, mainly because attitudes were more stable than knowledge and more resistant to change.…”
Section: Smoking-related Knowledge and Attitudesmentioning
confidence: 98%
“…Smoking knowledge and attitudes scores were often used as parameters of intervention effectiveness. However, most of these studies occurred in schools or primary care settings rather than in the workplace [34][35][36]. Similarly, some school-based intervention studies also found significant effects on changing both smoking-related knowledge and attitudes [34,35].…”
Section: Smoking-related Knowledge and Attitudesmentioning
confidence: 99%
“…40,41 However, despite improving children's knowledge and attitudes regarding the health hazards of tobacco smoke, some interventions did not succeed in creating a smoke-free home. 42,43 It seems that parents should also be directly involved in a schoolbased program to change in-home smoking behavior. Accordingly, the TLGS school-based intervention is a part of the TLGS community trial that targets children's behavior in the family context and not separately.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, some school‐based intervention changed parents' behaviors and, therefore had the potential to decrease in‐home smoking 40,41 . However, despite improving children's knowledge and attitudes regarding the health hazards of tobacco smoke, some interventions did not succeed in creating a smoke‐free home 42,43 . It seems that parents should also be directly involved in a school‐based program to change in‐home smoking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, some school-based intervention changed parents' behaviors and, therefore had the potential to decrease in-home smoking (33,34). However, despite improving children's knowledge and attitudes regarding the health hazards of tobacco smoke, some interventions did not succeed in creating a smokefree home (35,36). It seems that parents should also be directly involved in a school-based program to change in-home smoking behavior.…”
Section: Discussionmentioning
confidence: 99%